Assessment of transportation management system implementation - Gonçalves, Goreth C. [UNESP]; Tramarico, Claudemir L. [UNESP]; Marins, Fernando A. S. [UNESP] (My University, 2021)
The Transportation Management System (TMS) has helped many organizations to stand out and consolidate themselves in the market through a review of their processes and better optimization in the dynamics and distribution of internal activities. TMS has been a resource increasingly used by companies that seek a competitive differential in the market, such as: Cost reduction, increase customer service, response time, process reliability, less information lost across processes, requirements fulfillment, product traceability, faster and more efficient management of human resources and equipment. A complete assessment of TMS implementation should involve multiple criteria. Analytic Hierarchy Process (AHP) is worldwide multi-criteria analysis method. The purpose of this paper is analyzing the weaknesses in the logistics processes of a company in the educational field that has not yet adopted a computerized system for planning, scheduling and controlling the execution of transportation. The main contribution of this paper is to provide a proposal to obtaining an efficient management of the whole logistic process of transportation of confidential materials through TMS and identify their main logistics processes and qualify them to improve it with AHP application.
Keywords: Analytic Hierarchy Process; Logistics; Transportation Management System